The correlation between the mutual deletions of amino acids within porcine circovirus rep protein and the discrepancy of replication. (April 2018) - Zhang, Lingling; Wu, Xiaoyan; Shi, Jianli; Peng, Zhe; Zheng, Shuxuan; Xu, Shengnan; Han, Hong; Xin, Changxun; Liu, Yuwei; Gao, Mei; Yu, Jiang; Sun, Wenbo; et al.
Abstract: Porcine circovirus (PCV) has two potential open reading frames, ORF1 and ORF2. ORF1 is predicted to encode a replication-associated protein (Rep) essential for replication of viral DNA. In some studies, PCV1 replicated more efficiently in PK-15 cells than PCV2 was elucidated. PCV1 compared with PCV2; there is some amino acids' deficiency on Rep protein. To identify whether the above amino acids deletion affects the replication of PCV1 and PCV2, we constructed three double copy clones by overlap extension PCR. The 2PCV2(vV) clone deleted the valine of Rep protein in the backbone of PCV2 genome. The 2PCV2(dSGR) clone inserted serine, glycine and arginine of Rep protein successively in the backbone of PCV2 genome. The 2PCV2(dSGR&vV) clone inserted serine, glycine and arginine as well as deleted the valine of Rep protein in the backbone of PCV2 genome. These clones we constructed with amino acid mutations and parental DNA clones were all transfected in PK-15 cells that free of PCV contamination, and their growth characteristics in vitro were determined and compared, to evaluating the replication of the mutant infectious DNA clones. Our results showed that the double copy infectious clones with amino acid mutations could be rescued in vitro. The 2PCV2(vV) replicated more efficiently than parental viruses 2PCV2 and 2PCV1 but the replicated ability of 2PCV2(dSGR) and 2PCV2(dSGR&vV) is attenuated than parental viruses 2PCV2 and 2PCV1. We can determine the valine is the important amino acid that cause PCV1 replicated more efficiently in PK-15 cells than PCV2 primarily. These findings are benefit for exploring the mechanisms of viral replication in pigs and important implications for PCV2 vaccine development. Highlights: After 5th passages cultivating PCV1 has strong proliferative ability than PCV2. We found some amino acids are mutual deletion on Rep protein between PCV1 and PCV2. We constructed three double copy clones successfully to testing our assumption. 2PCV2(vV) replicated more efficiently in PK-15 cells than parental clones. 2PCV2(dSGR) and 2PCV2(dSGR&vV) replicated less in PK-15 cells than parental clones.